Individual and combined effects of heavy metals on ’survival aud biochemistry of Oreoclzromis mossambicus - James, R; Sampath, K; Sivakumar, V; Manthiramoorthy, S (Indian Journal of Fisheries, 2011)
Information about the combined effects of heavy metals on survival aocl biochemistry of fISh being ty, the preSent swdy on effects of copper, zinc and cadmium on survival and biochemical compositiOn of the fish Oreochromis mossambicus. was undertaken.